(untitled) (Historia, 2021)
Sidney Bunting - a founder member of the Communist Party of South Africa (CPSA) and a leading South African communist of the 1920s - was an extraordinary person who lived an extraordinary life. It was, indeed, so full of surprise and drama, that it might have merited a novel, not just an academic biography.